Analisis Efisiensi Teknis Program Jaminan Kematian (JKM) Bpjs Ketenagakerjaan Tahun 2020-2024 - Rizqi Eka Sukmayasa; Siti Jahroh; Heny Kuswanti Suwarsinah (LPPM Institut Pendidikan Nusantara Global, 2026)
The Social Security Administering Agency (BPJS Ketenagakerjaan) is a public legal entity that administers the employment social security program, with relatively good financial performance in terms of contribution revenue, investment returns, and assets. However, in terms of claims, the Death Benefit Program (JKM) has shown the highest claims ratio compared to other programs over the past five years. In some months, the number of claims paid even exceeded contribution revenue, and there was a downward trend in the program's financial health. This study aims to measure the technical efficiency of JKM implementation for the 2020–2024 period, analyze factors influencing efficiency, and formulate policy recommendations. Fifty-one monthly Decision-Making Units (DMUs) were analyzed using Data Envelopment Analysis (DEA), followed by Tobit regression to identify the determinants of efficiency. The results indicate varying levels of technical efficiency, with 29 of the 51 months experiencing inefficiency. Investment yield, active participant growth, and the claims ratio had a positive and significant impact on efficiency, while the COVID-19 pandemic had no significant impact. Recommendations include strengthening investment management, expanding active participation, and evaluating contribution rates to maintain actuarial adequacy and program sustainability.